Realism in International Trade Relations: Limiting Judicial Activism - Dmytro Skrynka (Polish Political Science Yearbook)
The WTO dispute settlement system crisis is an important milestone in the history of international law. Since the realist school in the study of international relations is known for its attention to the limits of the functions of international law, it is quite appropriate to review the key concepts of the realist school relevant to the current crisis. The ambitious endeavor to minimize the use of political methods of dispute settlement in international trade disputes within the institutional system of the WTO has not been quite successful. As postulated by realists, the political processes prevailed over the international legal procedures. In this article, based on the realist approach, the causes of the stalemate of the WTO dispute settlement system are analyzed, and recommendations are presented for remedying the current situation. The comparative analysis method is used for this. The article translates the relevant concepts of international relations by key realists, including the classification of international disputes by Hans Morgenthau, into specific recommendations for resolving the ongoing crisis.